The Carolyne Project: A Speculative Experiment of Narrative Structure - James, Connor (My University, 2023)
The Carolyne Project is an in-progress exploration of different narrative structural shapes, moving away from the most common form in English literature: the wave or rollercoaster. Set in a post-climate cyberpunk landscape, the narrative uses a Möbius-fractal pattern to explore concepts of what it is to be human, both literally and metaphysically, through the lens of an undying character, Carolyne, while criticizing destructive capitalist structures and ideologies. To do so, the Möbius-fractal is the movement across the chronology of Carolyne’s life. Chapters alternate between the “left” strip moving forward, the “right” strip moving backward, and repeatedly overlapping at a single point key to the character’s formation. Using short chapters to leap across time to follow different key moments and deaths in Carolyne’s life, this creates an erratic narrative pulled together by cohesive but episodic chapters.
Thesis (Master's)--University of Washington, 2023
Keywords: Cyberpunk; Narrative shape; Narrative structure; Creative writing